Field evaluation of the performance of a SARS-CoV-2 antigen rapid diagnostic test in Uganda using nasopharyngeal samples. (March 2021) - Nalumansi, Aminah; Lutalo, Tom; Kayiwa, John; Watera, Christine; Balinandi, Stephen; Kiconco, Jocelyn; Nakaseegu, Joweria; Olara, Denis; Odwilo, Emmanuel; Serwanga, Jennifer; Kikaire, Bernard; Ssemwanga, Deogratius; et al.
Highlights: High global demand for SARS-CoV-2 testing to identify COVID-19 cases. qRT-PCR recommended diagnostic test but constraints such as cost prevent its use. Simple, low cost, and easy-to-use rapid antigen diagnostic tests urgently required. STANDARD Q COVID-19 Ag test exhibits less than optimal performance. Test may be used when molecular testing access is poor but qRT-PCR still required. Abstract: Objectives: There is a high demand for SARS-CoV-2 testing to identify COVID-19 cases. Real-time quantitative PCR (qRT-PCR) is the recommended diagnostic test but a number of constraints prevent its widespread implementation, including cost. The aim of this study was to evaluate a low cost and easy to use rapid antigen test for diagnosing COVID-19 at the point of care. Methods: Nasopharyngeal swabs from suspected COVID-19 cases and low-risk volunteers were tested with the STANDARD Q COVID-19 Ag Test and the results were compared with the qRT-PCR results. Results: In total, 262 samples were collected, including 90 qRT-PCR positives. The majority of samples were from males (89%) with a mean age of 34 years and only 13 (14%) of the positives were mildly symptomatic. The sensitivity and specificity of the antigen test were 70.0% (95% confidence interval (CI): 60–79) and 92% (95% CI: 87–96), respectively, and the diagnostic accuracy was 84% (95% CI: 79–88). The antigen test was more likely to be positive for samples with qRT-PCR Ct values ≤29, with a sensitivity of 92%. Conclusions: The STANDARD Q COVID-19 Ag Test performed less than optimally in this evaluation. However, the test may still have an important role to play early in infection when timely access to molecular testing is not available but the results should be confirmed by qRT-PCR.